3D Printing of Hierarchically Porous Lattice Structures Based on Åkermanite Glass Microspheres and Reactive Silicone Binder - Arish Dasan; Jozef Kraxner; Luca Grigolato; Gianpaolo Savio; Hamada Elsayed; Dušan Galusek; Enrico Bernardo (Journal of Functional Biomaterials, 2022)
The present study illustrates the manufacturing method of hierarchically porous 3D scaffolds based on åkermanite as a promising bioceramic for stereolithography. The macroporosity was designed by implementing 3D models corresponding to different lattice structures (cubic, diamond, Kelvin, and Kagome). To obtain micro-scale porosity, flame synthesized glass microbeads with 10 wt% of silicone resins were utilized to fabricate green scaffolds, later converted into targeted bioceramic phase by firing at 1100 °C in air. No chemical reaction between the glass microspheres, crystallizing into åkermanite, and silica deriving from silicone oxidation was observed upon heat treatment. Silica acted as a binder between the adjacent microspheres, enhancing the creation of microporosity, as documented by XRD, and SEM coupled with EDX analysis. The formation of ‘spongy’ struts was confirmed by infiltration with Rhodamine B solution. The compressive strength of the sintered porous scaffolds was up to 0.7 MPa with the porosity of 68–84%.